Understanding the T cell immune response in SARS coronavirus infection - Janice Oh, Hsueh-Ling (Nature Publishing Group, 2012)
The severe acute respiratory syndrome (SARS) epidemic started in late 2002 and swiftly spread across 5 continents with a mortality rate of around 10%. Although the epidemic was eventually controlled through the implementation of strict quarantine measures, there continues a need to investigate the SARS coronavirus (SARS-CoV) and develop interventions should it re-emerge. Numerous studies have shown that neutralizing antibodies against the virus can be found in patients infected with SARS-CoV within days upon the onset of illness and lasting up to several months. In contrast, there is little data on the kinetics of T cell responses during SARS-CoV infection and little is known about their role in the recovery process. However, recent studies in mice suggest the importance of T cells in viral clearance during SARS-CoV infection. Moreover, a growing number of studies have investigated the memory T cell responses in recovered SARS patients. This review covers the available literature on the emerging importance of T cell responses in SARS-CoV infection, particularly on the mapping of cytotoxic T lymphocyte (CTL) epitopes, longevity, polyfunctionality and human leukocyte antigen (HLA) association as well as their potential implications on treatment and vaccine development.